2009
DOI: 10.1590/s1413-78522009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Cultura de condrócitos em arcabouço tridimensional: hidrogel de alginato

Abstract: OBJETIVOS: O presente estudo teve como objetivo cultivar condrócitos retirados da articulação do joelho de coelhos encapsulados em hidrogel de alginato (HA) e caracterizar a produção de matriz extracelular (ECM). MÉTODOS: A cartilagem articular foi removida do joelho de coelhos, com três a seis meses, fragmentada em pedaços de 1mm e submetida à digestão enzimática. Uma concentração de 1x106 céls/mL foram ressuspensas em uma solução de alginato de sódio a 1,5% (w/v), em seguida fez-se o processo de gelatinizaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…Similar results to the present study were observed using 10 4 cells per microcapsules, through maintenance and cell proliferation for up to 4 weeks. With similar methodology to the present study, using 10 4 cells per microcapsules, was observed through maintenance and cell proliferation for up to 4 weeks [ 30 ]. Studies that performed the encapsulation of MSC from human bone marrow, at the concentration of sixty thousand cells per alginate microcapsule, reported that viability remained high (> 90%) over 4 weeks and the duration of culture in vitro had no effect on the cell viability [ 37 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similar results to the present study were observed using 10 4 cells per microcapsules, through maintenance and cell proliferation for up to 4 weeks. With similar methodology to the present study, using 10 4 cells per microcapsules, was observed through maintenance and cell proliferation for up to 4 weeks [ 30 ]. Studies that performed the encapsulation of MSC from human bone marrow, at the concentration of sixty thousand cells per alginate microcapsule, reported that viability remained high (> 90%) over 4 weeks and the duration of culture in vitro had no effect on the cell viability [ 37 ].…”
Section: Discussionmentioning
confidence: 90%
“…A study using six different types of comercial alginate demostrated that type may influence chondrocyte culture upon finding variation in their pH, viscosity or n-gururonic acid-manuronic acid ratio [ 39 ]. Researchers confirmed that variations alginate concentration influence the cellular metabolism and diffusion of the necessary components of the culture medium, recommending the use of 1.5% (w/v) [ 30 ]. Needle diameter may interfere with cell viability, concluding that larger gauge (19G) needles for cell implantation reduce the loss of stress-induced viability compared to smaller (21G and 23G) needle gauges [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells producing the anti‑angiogenic protein endostatin have been encapsulated in ultrapure alginate and implanted into the brains of dogs being treated for spontaneous brain cancer [84,85,86]. Many other cell types have been immobilized in alginate such as adipose-derived stem cells [87,88], mesenchymal stem cells [89,90], and chondrocytes [91,92]. …”
Section: 3d Cell Culturementioning
confidence: 99%
“…Even though a cell is usually able to overcome small disturbances of the redox balance, larger-scale disturbances may be lethal to the cells [17][18][19] , such the apoptosis caused by oxidative stress resulting from LED irradiation 17 . Our research group has been interested in suitable scaffolds for tissue engineering for a long time 12,20,21 . This paper describes different techniques of cell removal from tracheae as a proposed three dimensional scaffold, by associating traditional approaches with the novel LED proposal.…”
Section: Introductionmentioning
confidence: 99%